PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN IMPLIKASINYA TERHADAP KINERJA - Barin Barlian; Luthfi Maolani (JURNAL EKONOMI PERJUANGAN, 2022)
Abstract The purpose of this study was to determine and analyze the effect of emotional intelligence, spiritual intelligence on organizational citizenship behavior and its implications for employee performance both partially and simultaneously at the Regional Secretariat of Tasikmalaya Regency. The research method used is path analysis. Data collection is obtained through observation, questionnaires and literature. The object under study is the Regional Secretariat Staff of Tasikmalaya Regency. The population in this study were 194 employees.The results showed that Emotional Intelligence, Spiritual Intelligence and Organizational Citizenship Behavior had a significant effect both partially and simultaneously on the Employee Performance of the Regional Secretariat of Tasikmalaya Regency. Keywords: Emotional Intelligence, Spiritual Intelligence, Organizational Citizenship Behavior and Performance